The Clinical Features and Predictive Factors of Nocturnal Enuresis in Adult Women - Song, Qi-Xiang; Li, Jiayi; Gu, Yiyuan; Xu, Lei; Abrams, Paul; Xue, Wei (Frontiers in Medicine, 2022)
Objective: Our current knowledge on nocturnal enuresis (NE) in adults is scarce due to its uncommon nature. The present study was designed to investigate symptom characteristics and risk factors of NE in adult female in order to improve the current clinical understanding and management of this rare disease. Methods: Over a three-year period, we enrolled 70 adult women who complained bedwetting, with a frequency of at least once per week and a symptom duration of 3 months or longer. Patients were excluded if they had known pregnancy, current urinary tract infection, untreated malignancies, anatomical abnormalities and irregular sleep cycle. The International Consultation on Incontinence Modular Questionnaire - female lower urinary tract symptoms and bladder diary were employed to appraise lower urinary tract symptoms and voiding behavior. Urodynamics was performed to assess bladder function. Linear regression analysis was applied to determine potential risk factors for NE frequency. Results: Among the recruited subjects, comorbidities and lower urinary tract symptoms were frequently reported. On bladder diary, patients commonly presented with nocturnal polyuria (NP), reduced nocturnal voided volumes (RNVVs) or both. Urodynamics revealed multiple dysfunctions, namely detrusor overactivity (DO), urodynamic stress incontinence (USI), reduced compliance, bladder outlet obstruction, detrusor underactivity (DU) and simultaneous DO and DU. Patients with more frequent NE (≥4/week) demonstrated markedly increased body mass index, more comorbid conditions, worse incontinence symptom, NP or NP plus RNVVs, reduced compliance, and poorer voiding possibly owing to DU. Whereas, RNVVs alone and worse overactive bladder related parameters were associated with milder NE. Multivariate analysis indicated that frequency/urgency quality of life, incontinence symptom, NP + RNVVs, poor flow, increased bladder sensation, USI, and simultaneous detrusor overactivity plus DU were independent risk factors for NE severity. Conclusions: NE in adult women may have both urological and nonurological pathophysiology. Imbalanced circadian urine production, jeopardized continence mechanisms, overactive bladder and DU-induced poor voiding are major factors contribute to the pathogenesis of NE in adult women. Focused treatments on restoring these functions should be individually considered.